Magnetotransport and lateral confinement in an InSe van der Waals heterostructure - Lee, Yongjin; Pisoni, Riccardo; Overweg, Hiske; Eich, Marius; Rickhaus, Peter; Patane, Amalia; Kudrynskyi, Zakhar; Kovalyuk, Zakhar D.; Gorbachev, Roman; Watanabe, Kenji; Taniguchi, Takashi; Ihn, Thomas; et al. (IOP Publishing, 2018)
In the last six years, Indium selenide (InSe) has appeared as a new van der Waals heterostructure platform which has been extensively studied due to its unique electronic and optical properties. Such as transition metal dichalcogenides (TMDCs), the considerable bandgap and high electron mobility can provide a potential optoelectronic application. Here we present low-temperature transport measurements on a few-layer InSe van der Waals heterostructure with graphene-gated contacts. For high magnetic fields, we observe magnetoresistance minima at even filling factors related to two-fold spin degeneracy. By electrostatic gating with negatively biased split gates, a one-dimensional channel is realized. Close to pinch-off, transport through the constriction is dominated by localized states with charging energies ranging from 2 to 5 meV. This work opens new possibility to explore the low-dimensional physics including quantum point contact and quantum dot.